Maine sporting camps - Smith, George, 1948- (Down East Books, 2016)
In this guide, George Smith profiles the 50 or so sporting camps that are still in operation in Maine. He includes interviews with the staff and owners and gives his own experiences staying at each camp. Each entry also includes pertinent information on amenities, services offered, seasons and times of operation, as well as directions. If you're looking to get away from it all in Maine, this guide will help you find the road less traveled.